The Degree of Practicing of the Sixth Primary Social Studies’ Teachers in Iraq for the Principles of Active Learning from their Point of view (Journal of the College of Education for Women, 2019)
This study aimed to explore The Degree of Practicing of the Sixth Primary Social Studies’ Teachers in Iraq for the Principles of Active Learning from their Point of viewThe study society consisted of 230 male and femalesocial studiesteachers’ subjects for the sixth primary grade in Al-Anbar General Directorate of Education. 160 of them were selected to represent the sample of the study with a percent of (70%) from the original society. To achieve the aims of the study, the researchers prepared a questionnaire consisting of (43) items which represented the active learning principles. The validity and stability of the tool were verified. The researchers used the descriptive approach to suit the objectives of this study. The results of the study showed that the average of the social studies teachers' practice of the principles of active learning on the total tool was medium.Nine principles were practiced in a medium level and six principles were practiced at a low level. The results revealed that there were no statistically significant differences between the average values ​​of social teachers to the extent of practicing active learning principles due to the gender variable.